385 Safety and antitumor activity of dostarlimab in patients (PTS) with advanced or recurrent DNA mismatch repair deficient (DMMR) or proficient (MMRP) endometrial cancer (EC): results from the garnet study. (4th December 2020) - Oaknin, Ana; Gilbert, Lucy; Tinker, Anna V; Sabatier, Renaud; Boni, Valentina; O'malley, David M; Ghamande, Sharad; Guo, Wei; Im, Ellie; Pothuri, Bhavana
Abstract : Introduction/Background: Dostarlimab is a humanised programmed death (PD)-1 receptor monoclonal antibody that blocks interaction with the PD-1 ligands, PD-L1 and –L2. GARNET is a phase 1 study assessing antitumour activity and safety of dostarlimab monotherapy in patients with advanced solid tumours. Methodology: This multicentre, open-label, single-arm study is being conducted in 2 parts, dose escalation and expansion. Here we report on 2 independent expansion cohorts of patients with recurrent or advanced endometrial cancer (EC) that progressed on or after a platinum-based chemotherapy regimen. Assignment to cohort A1 (mismatch mutation repair deficient [dMMR] EC) or cohort A2 (mismatch mutation repair proficient [MMRp] EC) was determined by immunohistochemistry (IHC) testing. Patients received 500 mg dostarlimab intravenously once every 3 weeks for 4 cycles, then 1000 mg once every 6 weeks until disease progression, discontinuation or withdrawal. The primary endpoints are objective response rate (ORR) and duration of response (DOR) by blinded independent central review using RECIST version 1.1. Results: In total, 126 dMMR and 145 MMRp pts identified by IHC were enrolled and dosed. Of these, 103 dMMR and 142 MMRp pts had measurable disease as baseline and sufficient follow-up time (6 months) for efficacy analyses, respectively. Patients that progressed prior to 6 months were included in the evaluable population. ORR for dMMR EC was 44.7%; ORR for MMRp EC was 13.4% (table 1 ). Median DOR and OS were not reached in either cohort. Overall, 15 pts (5.5%) discontinued treatment due a TRAE (5 dMMR, 10 MMRp). Safety by cohort and overall are shown in table 2 . There were no deaths attributed to dostarlimab. Conclusion: Dostarlimab demonstrated durable antitumour activity in both dMMR and MMRp advanced/recurrent EC. dMMR status by IHC was associated with a higher response rate. Dostarlimab demonstrated a notable disease control rate (35.2%; 2.1% complete response, 11.3% partial response, 21.8% stable disease) in patients with MMRp EC, which comprised a higher percentage of patients with Type II EC and is historically associated with a worse prognosis. No new safety signals were detected. These cohorts are the largest prospective evaluation of a PD-(L)1 therapy in EC to date. Disclosures: Clinical trial registration: NCT02715284 This study was sponsored by GlaxoSmithKline, Waltham, MA, USA. Dr. Oaknin reports consulting and honoraria from AstraZeneca, Tesaro, Clovis, PharmaMar, and Roche. Dr. Gilbert reports honoraria from Meck, AstraZeneca, and Pfizer. Dr. Tinker reports grants and personal fees from AstraZeneca. Dr. Sabatier reports grants from EISAI and AstraZeneca; personal fees from Roche, Pfizer, Tesaro, Novartis and AstraZeneca; and non-financial support from Roche, Pfizer, AstraZeneca, and Amgen. Dr. O'Malley reports personal fees from Immunogen, Eisai, Agenus, GSK : Consultant/Advisory Board for Clovis, Ambry, Abbvie, Janssen/J&J, Regeneron, Novacure, Myraid Genetics, Tarveda, Amgen, VentiRx, Array Biopharma, EMD Serono, Ergomed; Steering committee for Genentech/Roche and Merck; Institutional funding from Ajinomoto Inc, Ludwig Cancer Research, Stemcentrx, Inc, CERULEAN PHARMA, GOG Foundation, BMS, Serono Inc, TRACON Pharmaceuticals, Yale University, New Mexico Cancer Care Alliance, INC Research, Inc., Inventiv Health Clinical, Iovance Biotherapeutics, Inc, and PRA International. Dr. Ghamande reports consulting fees from Seattle Genetics; speakers' bureau fees from GSK; and institutional grants from GSK, Merck, Roche, Genentech, Takeda, Seattle Genetics, Advaxis, BMS, Clovis, Abbvie, and Tesaro. Dr. Pothuri reports grants, personal fees and non-financial support from GSK; Advisory Board fees from AstraZeneca and Clovis Oncology. Dr. Boni has nothing to disclose. Drs. Guo and Im are employees of GlaxoSmithKline.